Financial adversity and subsequent health and wellbeing during the COVID-19 pandemic in the UK: A qualitative interview study - Tom May; Henry Aughterson; Daisy Fancourt; Alexandra Burton (Elsevier, 2023)
Aims: There are concerns that the economic impacts of the COVID-19 pandemic, including employment inactivity and job loss, will have consequences for the UK population's health and wellbeing. However, there is limited qualitative research into how financial adversity contributes to poor health outcomes in this context. This study aimed to explore forms of financial adversity experienced during the pandemic and their subsequent impacts for health and wellbeing. Methods: Qualitative semi-structured interviews with 20 people who experienced a form of financial adversity during the pandemic and six service providers employed in social welfare support services. Data were analysed using reflexive thematic analysis. Results: Two main sources of financial adversity were identified: reductions in household incomes and increased living costs which engendered emotional and physical burdens. Coping strategies included increased financial borrowing, support from informal and formal networks and cutting back on energy use, food and non-essential items. Conclusion: Our study highlighted exposure to multiple financial adversities because of the pandemic and how these experiences led to poor mental and physical health. The findings underline the importance of measures attending to the immediate needs of individuals, including accessible, co-located financial and psychological services, as well as broader measures that seek to reduce social and economic inequalities.